In-situ Mechanical Characterization of Abdominal Muscle Using Stereo Imaging - Simón-Allué, Raquel; Agudo, Antonio; Montiel, J.M.M.; Calvo, Begoña (Jornada de Jóvenes Investigadores del I3A, 2017)
We present a method to characterize in vivo the mechanical behavior of abdominal muscle, using inverse finite element analysis and image processing algorithms to estimate the properties. The aim of this technique is to help surgeon to choose the hernia mesh that better reproduces the mechanical behavior of the healthy muscle.